Dictionary of Islam : being a Cyclopaedia of the Doctrines, Rites, Ceremonies, and Customs, Together with the technical and Theological terms, of the Muhammadam Religion - Thomas Patrick Hughes (Cosmo Publications)
tr, c.1-3/stoc5.c1&c.3/c.1/ada dua cantuman dg judul beda sedikit